Developing a Value-Focused Thinking and Analytic Hierarchy Process-Based Strategic Decision-Making Framework for Managing High Salt Content Crude Oil in Refinery Operations - Fakhrul Ferdian; Utomo Sarjono Putro (Eduvest - Journal of Universal Studies, 2026)
The government's policy to maximize domestic crude oil absorption has placed a Refinery in Indonesia in a complex strategic position, particularly due to the increasing requirement to process high-salt-content crude oil. This condition introduces significant risks to equipment reliability, process stability, and operational efficiency, requiring more robust and structured decision-making capabilities. This study aims to identify key barriers in strategic decision-making, develop an improved framework, and evaluate its effectiveness in addressing the high-salt crude challenge. A mixed-methods sequential exploratory approach is applied, combining qualitative analysis — including SWOT, Five-Why, interviews, focus group discussions, and Value Focused Thinking (VFT) — with quantitative evaluation using the Analytic Hierarchy Process (AHP). VFT is used to define decision objectives and generate strategic alternatives, while AHP structures decision criteria, assigns weights, and prioritizes alternatives. The results show that the key barriers to decision-making are predominantly systemic, including governance inconsistency and lack of integrated evaluation criteria. The developed VFT–AHP-based framework introduces four main decision criteria, namely Operational Excellence, Process Stability, Economic Performance, and Strategic Feasibility, and evaluates four strategic alternatives. The AHP results indicate that new desalter installation is the highest-ranked alternative (32.9%). Sensitivity analysis demonstrates that the ranking is robust under ±20% variation in criteria weights, confirming model stability. Furthermore, the proposed framework improves decision clarity, consistency, and transparency by transforming a fragmented and binary decision process into a structured multi-criteria evaluation system. Management validation confirms that the framework is practical to implement and enhances accountability and defensibility under regulatory and audit scrutiny.